Various Policies of PT Garuda Indonesia (Persero) Tbk. in Increasing Its Productivity, Efficiency and Income - Tyana; Alfin Mohammad Abdillah (Journal Of Social Research, 2021)
At the micro-economic level, companies, both small and large, often make policies to deal with economic challenges. This policy aims to create a company that can achieve a sustainable level and increase its productivity and efficiency. PT Garuda Indonesia has issued a microeconomic policy to support its business continuity, but there are still some policies that are not in line with the company's ultimate goal. This essay will explain the problems faced by PT Garuda Indonesia (Persero) Tbk. and analyze the effectiveness of the policies that have been made. The aim is to provide an overview of the business continuity of PT Garuda Indonesia (Persero) Tbk. and its ability to face the current global challenge, namely the COVID-19 pandemic.